International knowledge spillovers through high-tech imports and R&D of foreign-owned firms - Heike Belitz; Florian Mölders (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
The international transmission of knowledge through import spillovers, as a source of TFP growth, has received much attention in the literature. We investigate two additional direct channels through which R&D disseminates: the import of high-technology goods and the internationalization of business R&D. Building on an extensive dataset, covering both developing and industrial countries, we add foreign owned patents as a proxy for R&D activities of multinationals. While we confirm the significance of import spillovers for all countries included, we find additional spillovers for developing countries through the import of high-technology goods. Only developed economies seem to benefit from the diffusion of knowledge that originates through cross-border cooperation in R&D by multinationals.
Keywords: F14; F23; O47; 330; Productivity growth; Technology diffusion; Multinational enterprise